Ensuring the determinant of waqf in Indonesia: Does religiosity matter? - Achmad Nurdany (Faculty of Economics, Universitas Islam Indonesia, 2019)
This paper examines the determinant of waqf (Islamic Endowment) in form of land in Indonesia. The study used cross-section data analysis from 33 Provinces provided by Ministry of Religious Affairs Republic of Indonesia in 2016. This paper proposed a model and developed a hypothesis that the total number of land waqf in Indonesia will be determined by the ratio of Muslims to total population, the number of mosques and the number of clerics. The results showed that the impact toward waqf varies among independent variables. The ratio of Muslims does not have any relation to the waqf even though the regression coefficient is positive. The number of mosques has a negative impact, while the positive relationship only found in the number of clerics. For that reason, some policy recommendations are also discussed.